2011
DOI: 10.1016/j.biocon.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Food for thought: Risks of non-native species transfer to the Antarctic region with fresh produce

Abstract: International audienceTo understand fully the risk of biological invasions, it is necessary to quantify propagule pressure along all introduction pathways. In the Antarctic region, importation of fresh produce is a potentially high risk, but as yet unquantified pathway. To address this knowledge gap, >11,250 fruit and vegetables sent to nine research stations in Antarctica and the sub-Antarctic islands, were examined for associated soil, invertebrates and microbial decomposition. Fifty-one food types were sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…Modified with permission from Thorp and Lynch (2000) 2008; Essl et al 2015). For example, a risk assessment of pathways into the Antarctic found high propagule loads for fresh produce (especially leafy produce; Hughes et al 2011), infrastructure development activities, and entrainment on the clothing of visiting tourists and scientists (Chown et al 2012). This knowledge has allowed five particular pathways of introduction to the region to be prioritized for management (COMNAP 2014).…”
Section: Prioritizing Invasion Pathwaysmentioning
confidence: 99%
“…Modified with permission from Thorp and Lynch (2000) 2008; Essl et al 2015). For example, a risk assessment of pathways into the Antarctic found high propagule loads for fresh produce (especially leafy produce; Hughes et al 2011), infrastructure development activities, and entrainment on the clothing of visiting tourists and scientists (Chown et al 2012). This knowledge has allowed five particular pathways of introduction to the region to be prioritized for management (COMNAP 2014).…”
Section: Prioritizing Invasion Pathwaysmentioning
confidence: 99%
“…With a considerable expansion of scientific expeditions and supporting logistics, as well as a remarkable rise of tourism in XXI century, the risk of alien species invasion increased. There is a significant number of tourists visiting the Antarctic, particularly the Scotia Arc region, but a scientific expedition bringing huge amount of cargo and equipment creates considerably higher impacts on the terrestrial ecosystems (Hughes et al 2011;Chwedorzewska and Korczak 2010). Most stations and bases have a high probability of causing adverse influences on the terrestrial ecosystems due to their localization in coastal ice-free areas, which are also favourable to biological communities (Rakusa-Suszczewski and Krzyszowska 1991; Terauds et al 2012).…”
mentioning
confidence: 99%
“…Hughes et al (2011) identified 19 spe− cies of fungi on rotting fruit and vegetables, also on the packaging and associated soil, most of which have previously been reported in different regions of the Ant− arctic. However, approximately 30% of them were not recorded previously from continental Antarctica and the Antarctic Peninsula.…”
Section: Introductionmentioning
confidence: 91%
“…An excellent vector for the transfer of fungal and other propagules to and within Antarctic regions is via humans and associated cargo, including food (Whinam et al 2005;Chwedorzewska 2009;Hughes et al 2011;Lityńska−Zając et al 2012;Chwedorzewska et al 2013). Hughes et al (2011) identified 19 spe− cies of fungi on rotting fruit and vegetables, also on the packaging and associated soil, most of which have previously been reported in different regions of the Ant− arctic.…”
Section: Introductionmentioning
confidence: 99%